Hierarchical Construction of Znbi2o4 Anchored on Flower-Like Bi2wo6 Heterojunction Photocatalyst for Removal of Alizarin Red S - Radhalayam, D (Elsevier B.V., 2025)
In this study, we investigated the fabrication and photocatalytic performance of ZnBi2O4@Bi2WO6 nanocomposites for the degradation of organic pollutants. The nanocomposites were synthesized via a hydrothermal method followed by ultrasonic treatment, resulting in a unique composite structure. X-ray diffraction (XRD) confirmed successful material synthesis, and scanning electron microscopy (SEM) revealed the morphologies of Bi2WO6 nanoflowers and ZnBi2O4 nanocubes, with the composites exhibiting a hybrid network-like structure. UV–visible spectroscopy showed a significant redshift in the optical absorption edge, indicating that ZnBi2O4 incorporation effectively reduced the band gap of the nanocomposite, enhancing its visible light absorption. Photoluminescence (PL) spectroscopy demonstrated that the nanocomposites promoted efficient charge separation and minimized recombination, critical factors for improved photocatalytic performance. Under visible light, the ZnBi2O4@Bi2WO6 nanocomposites achieved a degradation efficiency of 96.8 % for alizarin red S (ARS), following pseudo-first-order kinetics. The composites also exhibited excellent stability, with only a 6.05 % loss in activity after five degradation cycles, confirming their long-term durability. Trapping experiments identified hydroxyl radicals (·OH), holes (h+), and electrons (e–) as active species in the degradation mechanism. Overall, ZnBi2O4@Bi2WO6 nanocomposites show strong potential as efficient and stable photocatalysts for removing hazardous organic pollutants from wastewater, offering a sustainable solution for environmental cleanup. © 2025 Elsevier B.V.